2008
DOI: 10.1111/j.1742-4658.2008.06412.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning and characterization of two soybean protein disulfide isomerases as molecular chaperones for seed storage proteins

Abstract: Protein disulfide isomerase family proteins play important roles in the folding of nascent polypeptides and the formation of disulfide bonds in the endoplasmic reticulum. In this study, we cloned two similar protein disulfide isomerase family genes from soybean leaf (Glycine max L. Merrill. cv Jack). The cDNAs encode proteins of 525 and 551 amino acids, named GmPDIL‐1 and GmPDIL‐2, respectively. Recombinant versions of GmPDIL‐1 and GmPDIL‐2 expressed in Escherichia coli exhibited oxidative refolding activity f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(53 citation statements)
references
References 53 publications
0
53
0
Order By: Relevance
“…Studies on the rice mutant esp2 (endosperm storage protein 2), which exhibits unusually partitioned proteins and PBs, confirmed the causative role of PDI in the assortment of prolamins and proglutelins, as the mutant lacked the transcripts of PDI (OsPDIL1-1; LOC Os11g09280) (Takemoto et al 2002). Many soybean PDIs also function in storage protein folding and ER stress response, through enzymatic and chaperone activities and/or degradation of unfolded proteins Kamauchi et al 2008;Iwasaki et al 2009). …”
Section: Introductionmentioning
confidence: 97%
“…Studies on the rice mutant esp2 (endosperm storage protein 2), which exhibits unusually partitioned proteins and PBs, confirmed the causative role of PDI in the assortment of prolamins and proglutelins, as the mutant lacked the transcripts of PDI (OsPDIL1-1; LOC Os11g09280) (Takemoto et al 2002). Many soybean PDIs also function in storage protein folding and ER stress response, through enzymatic and chaperone activities and/or degradation of unfolded proteins Kamauchi et al 2008;Iwasaki et al 2009). …”
Section: Introductionmentioning
confidence: 97%
“…This family of proteins have ubiquitous expression across soybean tissues, are localized to the ER lumen in other tissues and are involved in the proper folding and quality control of storage proteins (71). Import of proteins into the symbiosome would likely require the same processes and, as the structure and composition of the SM is most closely related to the ER (3), these PDI proteins may have been co-opted for this role during the symbiosis.…”
Section: Soybean Symbiosome Proteomementioning
confidence: 99%
“…Protein disulfide isomerases play important roles in the formation of disulfide bonds in nascent proteins. Kamauchi et al (2008) characterized two PDILs in soybean (GmPDIL-1 and GmPDIL-2) that were suggested to be molecular chaperones involved in proper folding or quality of legumins. This may suggest a role for Lotus PDILs in disulfide bond formation in the LLPs.…”
Section: Protein Identificationsmentioning
confidence: 99%